Contract and the Code: the Case of Predictive Contracting - Cvetković, Predrag; Nikolić, Ljubica (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
Predictive contracting uses information technology tools to determine the correlation between contractual provisions and contract performance using external data; the ultimate goal of applying this method is to define the contract in a way that ensures its execution in accordance with the will of the parties. Parties may anticipate how the contractual provisions/terms (and the choice between them) relate to the outcome of the contract (with outcomes); those information can be used iteratively (in a repetitive process) in order the text of the contract to be improved. Predictive contracting consists of: (1) an analytical model and (2) a set of data on contract terms, outcomes, and external conditions. The analytical model should be defined in a way that is "readable" and understandable to the programmer who translates it into program code. The format of the data as a second fragment of predictive contracting must be suitable for algorithmic processing. Predictive contracting is applicable to simple contracts often concluded on the market: the reason for this limitation is that the model’s ability to predict outcomes decreases as the complexity of the subject of analysis (contracts) increases. Complex contracts remain outside the realm of predictive contracting. The predictive power of the analytical model is increased by increasing the amount of data that the model has access to. The premise on which predictive contracting is based is that a contract is a complex system of contractual provisions contained therein. The degree of complexity of the contract is proportional to the degree of interaction between the contract provisions: the greater the degree of these interactions, the more complex the contract is. Predictive contracting aims to help contractors anticipate the effects of contractual provisions on outcomes so that subsequent contracts can be improved in a way that allows for better outcomes. Improving contract outcomes is the ultimate goal of predictive contracting. Predictive contracting enables the issue of modification risk (which in the traditional sense is the subject of legal analysis and legal intuition) to be implemented in a procedurally defined, measurable and controlled manner. The application of predictive contracting is encouraged by the possibility of its automation and computer processing.